Integration of the Concept of Archipelagic State and Jou Se Ngofangare Customary Values in the Formation of Marine Policy in North Maluku - Fathurrahim; Chalil, Nurhayati (Candela Edutech Indonesia, 2025)
This research aims to analyze how the customary value of Jou Se Ngofangare functions as a source of social and moral legitimacy in implementing marine policy based on the Archipelagic State concept in North Maluku. The study arises from the existing gap between marine policies founded on national and international legal frameworks-such as UNCLOS 1982 and Law Number 6 of 1996 on Indonesian Waters-and the deeply rooted local wisdom of North Maluku’s indigenous communities. The Jou Se Ngofangare value, which emphasizes respect, justice, balance, and moral responsibility toward nature, is seen as a moral compass that can strengthen the legitimacy and contextual relevance of marine policies. The research highlights the urgency of integrating customary values into public policy to minimize social resistance and promote equitable, sustainable marine resource management. Using a normative legal method combined with a socio-legal approach, the study examines both formal legal norms and the living law embodied in customary practices. The findings reveal that Jou Se Ngofangare values play a crucial role in enhancing the effectiveness, community acceptance, and ethical grounding of marine policy implementation. However, challenges remain in the limited formal recognition of customary norms within regulatory frameworks and the weak coordination between government institutions and customary authorities. Ultimately, this research proposes an integrative model that bridges positive law with local wisdom, offering a contextualized and culturally rooted foundation for marine policy legitimacy in North Maluku.